TYPOLOGICAL ANALYSIS OF STUDENT MOTIVATION - Konstantin V. Rochev (Высшее образование в России, 2016)
The article describes the results of the survey of students’ motivation typology using the Gorchakov model. The survey covered the students of five courses of a specialty “Information systems andtechnologies”. The work shows the percentage distribution of the types of students’ motivation, presents the correlation analysis, and also describes the influence of the type of motivation on the average score. This research was carried out before the implementation of the index-rating estimation system and material stimulation for students for the purpose to estimate the influence of the system on the changes in students’ motivation.